2019
DOI: 10.1155/2019/6182397
|View full text |Cite
|
Sign up to set email alerts
|

Use of Cadaveric Pericardial Tissue in the Surgical Treatment of Neurogenic Bladder

Abstract: The surgical treatments for neurogenic bladder are extremely variable. The lack of specific treatment guidelines makes this disease process even more challenging to treat. We present a case of a 55-year-old female with neurogenic bladder secondary to spinal cord injury (SCI). Her incontinence was conservatively managed with indwelling Foley drainage. Despite continued upsizing of the Foley catheters, the patient continued to have urinary leakage. The patient subsequently underwent a transvaginal bladder neck c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…A paucity of studies exists on biologic grafts used in the setting of vesicovaginal fistulas. Caja et al reported on the use of CPT interposition to decrease the risk of vesicovaginal fistula formation [ 12 ]. Due to the low cost, ease of handling, and less immunogenicity, CPT may be used to help prevent fistula formation [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…A paucity of studies exists on biologic grafts used in the setting of vesicovaginal fistulas. Caja et al reported on the use of CPT interposition to decrease the risk of vesicovaginal fistula formation [ 12 ]. Due to the low cost, ease of handling, and less immunogenicity, CPT may be used to help prevent fistula formation [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Management of a neurogenic bladder case requires patient education and interventions such as manual expression, timed voiding, medicines, intermittent catheterizations, and indwelling urinary catheters, as well as surgical procedures [ 38 , 39 ]. A technique known as triggered reflex voiding involves stimulation of detrusor muscles by an externally elicited sacral reflex such as scratching the upper medial aspect of the thigh, suprapubic tapping or jabbing, or perineal manipulation and may be used to allow voiding.…”
Section: Reviewmentioning
confidence: 99%